Misadventures in archaeology : the life and career of Charles Conrad Abbott - Dillian, Carolyn D.; Bello, Charles A. (University of Pennsylvania Museum of Archaeology and Anthropology, 2020)
In the late nineteenth century, Charles Conrad Abbott, a medical doctor and self-taught archaeologist, gained notoriety for his theories on early humans. This is the first biography to address his archaeological research beyond the Paleolithic debate, including his attempts at historical archaeology on Burlington Island in the Delaware River.